HISTOPATHOLOGY OF THE LIVER IN WISTAR RATS WITH CHRONIC APICAL PERIODONTIS AFTER INTRACANAL MEDICATION - Ene, Theresia; Merdana, I Made; Winaya, Ida Bagus Oka; Widiadnyani, Ni Kadek Eka; Sudimartini, Luh Made (Buletin Veteriner Udayana; Vol. 15 No. 2 April 2023, 2023)
Dental disease is a problem that is common in Indonesia, and it affects around 96.58% of the population. The use of chemical drugs that can cause side effects in patients makes people start other alternative treatments by using natural ingredients namely meniran ( Phyllanthus niruri L ). This study examines the liver histopathology of Wistar rats with chronic apical periodontitis after administration of intracanal drugs. This study looked at the effects of a medicament paste on rats for a period of seven, fourteen, and twenty-one days. Experimental animals were adapted to chronic apical periodontitis by inducing Enterococcus faecalis into right maxillary molars for 21 days.On day 22, all drug treatment groups were opened with GIC and given the prescribed drug treatment, and then closed again with GIC. The observed variables were the presence of inflammatory cell infiltration, hyperemia, and necrosis. Data were analyzed using a non-parametric statistical Kruskal-Wallis test, and if there was a significant difference, it was continued with the Mann-Whitney test. The results of the study showed that there was no significant difference between the three treatment groups (P1, P2, P3) and there was a significant difference between P0 and the other two groups. However, the results of statistical analysis of necrosis observed by histopathology in the liver showed that there was no significant difference between P0, P1, P2 and P3 treatments (P>0.05).From the research results, it can be concluded that administration of meniran leaves ethanolic extract can improve liver histopathology in rats with chronic apical periodontitis.